1987
DOI: 10.1139/y87-325
|View full text |Cite
|
Sign up to set email alerts
|

Role of atrial natriuretic peptide and urinary cGMP in the natriuretic and diuretic response to central hypervolemia in normal human subjects

Abstract: The response of plasma atrial natriuretic peptide (ANP) and urinary cGMP excretion to central hypervolemia induced by water immersion was assessed twice in five healthy male subjects, once while immersed in water to the neck for 3 h and again on a control day. Plasma ANP and urinary cGMP were measured by radioimmunoassay. Compared with the control day, overall change in plasma ANP on the immersion day was significant (p less than 0.05). In response to water immersion, plasma ANP increased from a base-line leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…HR responses are similarly conflicting, with studies reporting increases (5,7,10,11,29,44) and decreases (14 -16, 22, 27, 33, 37, 38). Finally, MAP responses have also reported increases (5,33), decreases (25,32), or no change (10,16,31). These conflicting results are related to differences in methodology, in particular posture, the duration of immersion, and water temperature, as highlighted in a study by Park et al (33), all of which may elicit reflex changes.…”
Section: Discussionmentioning
confidence: 99%
“…HR responses are similarly conflicting, with studies reporting increases (5,7,10,11,29,44) and decreases (14 -16, 22, 27, 33, 37, 38). Finally, MAP responses have also reported increases (5,33), decreases (25,32), or no change (10,16,31). These conflicting results are related to differences in methodology, in particular posture, the duration of immersion, and water temperature, as highlighted in a study by Park et al (33), all of which may elicit reflex changes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cyclic GMP in many cases appears to be a sensitive marker for the action of ANP in humans. Leung et al [32] demonstrated that urinary cyclic GMP excretion rose significantly by the initial hour of immer sion and that this increase was sustained and, indeed, tended to increase during 3 h of immersion. Cessation of immersion was associated with a decline in cyclic GMP, although the levels continued to exceed that of the preimmersion hour.…”
Section: Urinary Cyclic Nucleotide Excretion During Immersionmentioning
confidence: 97%
“…Leung et al [32] demonstrated that water immersion in sodium-replete normal subjects was associated with a prompt doubling of ANP by 30 min of immersion with a 2-fold ANF = Atrial natriuretic factor; UnsV = urinary sodium excre tion; NR = not reported; FR = overnight fluid restricted. All studies investigated the subjects in the seated posture and in thermoneutral water (34.5 ± 0.5 °C).…”
Section: Effects O F Wi To the Neck On Plasma Anpmentioning
confidence: 99%
“…Because ANF release is mediated at least in part by atrial stretch (19), HWI has been found to increase pANF in normal subjects (20) and in cirrhotic patients (21-23). This rise in pANF levels is associated with a rise in levels of urinary 5' cyclic guanosine monophosphate (cGMP), its second messenger (23)(24)(25)(26), in normal subjects (24) and in cirrhotic patients with ascites (25). However, the natriuretic response to HWI in cirrhotic patients with ascites has allowed us to categorize them into two groups: responders and nonresponders (23).…”
Section: Laurence M Blendis'mentioning
confidence: 99%